2022
DOI: 10.1101/2022.02.07.479410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glycan shield of the ebolavirus envelope glycoprotein GP

Abstract: The envelope glycoprotein GP of the ebolaviruses is essential for host cell attachment and entry. It is also the primary target of the protective and neutralizing antibody response in both natural infection and vaccination. GP is heavily glycosylated with up to 17 predicted N-linked sites, numerous O-linked glycans in its disordered mucin-like domain (MLD), and three predicted C-linked mannosylation sites. Glycosylation of GP is important for host cell attachment to cell-surface lectins, as well as GP stabilit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Both protein-glycan and protein-protein clashes combine to inhibit N-linked glycan maturation, and oligomannose-type glycans are observed on viral glycoproteins that have exited the secretory system (Watanabe et al, 2019). This is most pronounced on the HIV-1 Envelope glycoprotein (Cao et al, 2017; Struwe et al, 2018); however they have been observed on Influenza HA (Lee et al, 2021), Lassa virus glycoprotein complex (Watanabe et al, 2018), Ebola glycoprotein (Peng et al, 2022), SARS-CoV-1 (Watanabe et al, 2020b), MERS-CoV (Watanabe et al, 2020b) and importantly SARS-CoV-2 (Allen et al, 2021; Brun et al, 2021; Watanabe et al, 2020a; Zhao et al, 2020). The presence of oligomannose-type N-linked glycans on the surface of the spike has been shown to be key indicators of the glycan shield density, and the extent to which the glycan shield occludes immunogenic protein epitopes (Allen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Both protein-glycan and protein-protein clashes combine to inhibit N-linked glycan maturation, and oligomannose-type glycans are observed on viral glycoproteins that have exited the secretory system (Watanabe et al, 2019). This is most pronounced on the HIV-1 Envelope glycoprotein (Cao et al, 2017; Struwe et al, 2018); however they have been observed on Influenza HA (Lee et al, 2021), Lassa virus glycoprotein complex (Watanabe et al, 2018), Ebola glycoprotein (Peng et al, 2022), SARS-CoV-1 (Watanabe et al, 2020b), MERS-CoV (Watanabe et al, 2020b) and importantly SARS-CoV-2 (Allen et al, 2021; Brun et al, 2021; Watanabe et al, 2020a; Zhao et al, 2020). The presence of oligomannose-type N-linked glycans on the surface of the spike has been shown to be key indicators of the glycan shield density, and the extent to which the glycan shield occludes immunogenic protein epitopes (Allen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This includes critical signaling proteins such as the type-I cytokine receptors [9][10][11] , myelin-associated glycoprotein 8 , adhesion GPCRs 7 and Wnt/β-catenin 12 . C-mannosylation is also found on important pathogen antigens, such as the soluble glycoprotein of Ebola virus 13,14 , and essential adhesins of apicomplexan parasites, including the toxoplasmosis-causing Toxoplasma gondii 15 and tools that allow addressing these questions have only recently been developed. These include synthetic C-mannosyl-tryptophan conjugates 24,25 , yeast-based high-throughput in vivo CMT-activity assays 26 , bacterial lectins 27 and monoclonal antibodies for the enrichment and mass spectrometric analysis of C-mannosylated peptides 26 .…”
mentioning
confidence: 99%